Targeting histone deacetylase 4/ubiquitin‐conjugating enzyme 9 impairs DNA repair for radiosensitization of hepatocellular carcinoma cells in mice. Issue 2 (26th December 2017) - Tsai, Chiao‐Ling; Liu, Wei‐Lin; Hsu, Feng‐Ming; Yang, Po‐Sheng; Yen, Ruoh‐Fang; Tzen, Kai‐Yuan; Cheng, Ann‐Lii; Chen, Pei‐Jer; Cheng, Jason Chia‐Hsien
Abstract : Several strategies to improve the efficacy of radiation therapy against hepatocellular carcinoma (HCC) have been investigated. One approach is to develop radiosensitizing compounds. Because histone deacetylase 4 (HDAC4) is highly expressed in liver cancer and known to regulate oncogenesis through chromatin structure remodeling and controlling protein access to DNA, we postulated that HDAC4 inhibition might enhance radiation's effect on HCC cells. HCC cell lines (Huh7 and PLC5) and an ectopic xenograft were pretreated with HDAC inhibitor or short hairpin RNA to knock down expression of HDAC4 and then irradiated (2.5‐10.0 Gy). We evaluated cell survival by a clonogenic assay; apoptosis by Annexin V immunofluorescence; γH2AX, Rad51, and HDAC4 by immunofluorescence staining; HDAC4, Rad51, and ubiquitin‐conjugating enzyme 9 (Ubc9) in HCC cell nuclei by cell fractionation and confocal microscopy; physical interaction between HDAC4/Rad51/Ubc9 by immunoprecipitation; and the downstream targets of HDAC4 knockdown by immunoblotting. Both HDAC4 knockdown and HDAC inhibitor enhanced radiation‐induced cell death and reduced homologous recombination repair of DNA double‐strand breaks and protein kinase B activation, leading to increased apoptosis. HDAC4 knockdown with or without an HDAC inhibitor significantly delayed tumor growth in a radiation‐treated xenograft model. Radiation stimulated nuclear translocation of Rad51 in an HDAC4‐dependent manner and the binding of Ubc9 directly to HDAC4, which led to Ubc9 acetylation. Moreover, these effects were accompanied by HDAC4/Ubc9/Rad51 complex dissociation through inhibiting nuclear translocation. Conclusion: HDAC4 signaling blockade enhances radiation‐induced lethality in HCC cells and xenografts. These findings raise the possibility that HDAC4/Ubc9/Rad51 complex in DNA repair may be a target for radiosensitization of HCC. (Hepatology 2018;67:586‐599).